The effect of feed pretreatment on membrane microfiltration of titanium dioxide dispersions by ceramic tubular membranes - Grulich, Miroslav; Mikulášek, Petr (My University, 2016)
The influence of coagulant type and operating parameters on crossflow microfiltration of aqueous dispersions of titanium dioxide has been examined. The experiments were carried out with a tubular ceramic microfiltration membrane with a nominal pore size of 0.1m at various operating parameters. Three chosen types of organic coagulants were used for a series of crossflow microfiltration experiments: polyacrylamide (PAM), poly(diallyldimethylammonium chloride) (PDADMAC), and poly(acrylamide-co-acrylic acid) partial sodium salt (PACA). The results of the experiments without coagulants showed that the flux initially declines rapidly and then stabilizes. The results also suggested that PDADMAC was a better coagulant for this system and its optimal concentration was 30mgl(-1). Finally, it was shown that pretreatment of the feed by PDADMAC resulted in a permeate flux that was more than three times higher than that obtained without any pretreatment. Moreover, there was a very positive effect of this coagulant on the particle size. Pretreatment by 30mgl(-1) PDADMAC led to an average particle size that was almost 18 times higher than that obtained without pretreatment. The other two coagulants did not produce such improvements: pretreatment of the feed by PAM increased the permeate flux by only 10%, while pretreatment by PACA gave even lower permeate flux than no pretreatment. This means that the results of various experiments have shown the need for careful selection of the coagulant due to their differing influences on the permeate flux. The relationship between the particle size of the dispersion and the permeate flux was found from the results of these experiments. A published mathematical model was used to estimate the permeate flux. The results of the experiments showed that the mathematical model was able to predict the steady-state permeate flux quite accurately in some cases.
Vliv předúpravy nástřiku na membránovou mikrofiltraci disperzí oxidu titaničitého pomocí keramických trubkových membrán
Keywords: microfiltration; titanium dioxide dispersions; ceramic tubular membranes; mikrofiltrace; disperze oxidu titaničitého; keramické trubkové membrány